Design study of the proposed 12slot-14pole field excitation flux switching machine (FEFSM) for hybrid electric vehicles - Yunus, Nazira (2014)
A new structure of field excitation flux switching motor (FEFSM) as an alternative candidate of non-Permanent Magnet (PM) machine for HEV drives is presented in this thesis. Design principles and initial performances of the proposed motor with 12 stator slots and 14 rotor pole are demonstrated. Initially, the coil arrangement tests are examined to validate the operating principle of the motor and to certify the zero rotor position. Furthermore, the profile of flux linkage,cogging torque, torque versus Ja at various Je characteristics and torque versus power characteristics are observed and analyzed based on 2D-finite element analysis (FEA). The improvement design is done by using the “deterministic optimization method” to achieve the restriction and spesification target compared to Interior Permenant Magnet Synchronous Machines (IPMSM) that used in HEV drives. “The results obtained show that proposed 12S-14P FEFSM achieved the target performance for maximum power, maximum torque density, maximum power density and machine weight, while the maximum torque is not achieved as a target. Therefore, by further design modification and optimization it is expected that the low cost motor will successfully achieved the target performances.